Neglected voices Peace in the Old Testament - Leiter, David A. (Scottdale Herald Press, 2007)
The Bible has a reputation for being about violence in the Old Testament and about peace in the New Testament. David A. Leiter deconstructs that oversimplified notion as he explores passages in which God calls for the making of peace. By identifying key t
Keywords: Peace - Biblical teaching